2016
DOI: 10.1136/neurintsurg-2016-012750
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with SOFIA as an intermediate catheter in mechanical thrombectomy for acute ischemic stroke

Abstract: Mechanical and aspiration thrombectomy with SOFIA is safe and effective with high revascularization rates. Its trackability, stability, and luminal size make SOFIA suitable for stroke intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…The enlarged inner lumen of the FG2 allowed for concomitant use of intermediate large-bore aspiration catheters for salvage techniques, as well as increased aspiration power. In previous studies, the use of an intermediate catheter and the 'Solumbra technique' have been reported to result in better clinical and radiological outcomes (20,21). Moreover, in the present study, the multivariate analysis revealed that the use of an intermediate catheter reduced the occurrence of distal emboli.…”
Section: Discussionsupporting
confidence: 66%
“…The enlarged inner lumen of the FG2 allowed for concomitant use of intermediate large-bore aspiration catheters for salvage techniques, as well as increased aspiration power. In previous studies, the use of an intermediate catheter and the 'Solumbra technique' have been reported to result in better clinical and radiological outcomes (20,21). Moreover, in the present study, the multivariate analysis revealed that the use of an intermediate catheter reduced the occurrence of distal emboli.…”
Section: Discussionsupporting
confidence: 66%
“…Our final rate of favorable mTICI (Ն2b) appears similar to those previously published because authors noted favorable recanalization rates between 86.9% and 94.1% with the Sofia catheter. [8][9][10][11] Gory et al 16 reported 89% of mTICI 2b/3 in a meta-analysis of the overall literature dealing with ADAPT using various kinds of DACs. In comparison, reperfusion rates among ADAPT major trails were 92% and 85.4%, respectively, in the COMPASS and ASTER trials.…”
Section: Angiographic Outcomementioning
confidence: 99%
“…Its braid and coil construction combines different softness segments with a distal inner lumen of 0.055-0.070 inches, respectively, in 5F and 6F Plus versions. Despite previous publications, [8][9][10][11] the safety and efficacy of this DAC in a large population with first-line Sofia use are yet to be reported.…”
mentioning
confidence: 92%
“…Intermediate catheters have been used as an effective system in various neurovascular procedures such as brain arteriovenous malformation embolization [ 5 6 12 ], the intracranial stenting procedure, or aneurysm embolization [ 2 4 8 9 ]. These catheters have been successfully used in various intra-arterial revascularization procedures as an aspiration catheter system or an effective intermediate catheter system for the delivery of stentrievers [ 13 14 15 16 ]. However, these catheters are not suitable to use as a sole guiding catheter system due to the lack of a sufficient supportive body segment.…”
Section: Discussionmentioning
confidence: 99%